Design a knowledge-based governance model in executive organizations - Seyedeh Sadaf Veshkaei Nejad; Mohammad Doustar; Esmaei Malekakhlagh; Keikhosro Yakideh (مدیریت راهبردی دانش سازمانی)
Nowadays, knowledge-based governance can have a valuable impact on improving the performance of both government and private institutions. However, there is a possibility of overlooking the influential factors on this type of governance. Therefore, adherence to the principles of knowledge-based governance can contribute to improving the situation of organizations, and society, allowing for the maximum utilization of individuals' abilities, reducing societal challenges, and ultimately pursuing the public welfare. This research has employed a qualitative methodology and is based on Grounded theory, using the approaches of Strauss and Corbin. The study population consists of experts familiar with the subject, with 12 of them being selected through purposive and snowball sampling methods for in-depth interviews. We used MAXQDA software to analyse the data. 302 codes are identified and placed in the 46 subcategories and 18 main categories, which are in 6 main categories under the headings of causal conditions, including sharing, creating, preserving and maintaining knowledge, competence of managers. background conditions, including creating infrastructure, structure organization and culture of the organization. Intermediate conditions include rules and procedures, performance evaluation, transparency, team building, recruitment and retention, planning and administration system. The innovation dynamic capability and development strategy are strategic conditions. The performance of the society, organization and the employees are the consequence. The central condition is knowledge-based governance. The Grounded approach and model design in executive organizations has a unique aspect and facilitate the implementation of knowledge governance in executive organizations of the country.